Mechanisms of resistance to chemotherapy and radiotherapy in hepatocellular carcinoma - Guo, Jiapei; Li, Leilei; Guo, Bin; Liu, Dianxing; Shi, Jun; Wu, Chuntao; Chen, Junmao; Zhang, Xiaowei; Wu, Jinghua (Translational Cancer Research; Vol 7, No 3 (June 27, 2018): Translational Cancer Research, 2018)
Hepatocellular carcinoma (HCC) is an inflammation-related malignant tumor that develops from underlying cirrhosis. As HCC is a common tumor seen in clinical practice, its prevention and treatment attract considerable attention. There is no doubt that surgical interventions, such as resection and transplantation, are the best methods of addressing early HCC. However, because HCC is difficult to diagnose early in the disease course, and most patients tend to be diagnosed at advanced stages and cannot undergo surgery. In terms of advanced HCC, conservative treatment strategies are usually useful. However, chemotherapy, such as local chemoembolization and targeted immunization, and radiotherapy, such as stereotactic body radiation therapy, meet the treatment bottlenecks caused by increased resistance, indicating that considerable effort is still needed to treat HCC due to its high morbidity and mortality. In addition, treatment efficacy depends on our ability to study the related mechanisms of resistance and develop new approaches for advanced HCC. Studies have focused on the variety of possible mechanisms of resistance in HCC, and some progress has been made in recent years. However, further exploration of the relationships and crosstalk between associated molecular factors may deepen the understanding of underlying pathogenic mechanisms to help overcome HCC resistance.